Implementasi Algoritma Dijkstra Pada Pencarian Rute Terpendek Objek Wisata - Rachman Perayoga; Purwono Hendradi; Agus Setiawan (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The tourism sector has an important role as a source of income to support regional or national economic growth. Indonesia has a variety of natural beauty, one of which is in Temanggung Regency, Central Java. This diversity also forms the need for clear information about the location and types of tourism available. Therefore, an information system is needed that can help find the best path to the tourist site. One efficient approach is through the Dijkstra algorithm to determine the nearest route. Through the determination of the most efficient route, it will certainly have a positive effect, because it can reduce operational budgets and can optimize better travel periods between destinations. To implement the Dijkstra algorithm on the website using the Rapid Application Development (RAD) Method. In the built system, users can see the nearest route point from the initial location to the intended tourist spot, so it is expected to help users in terms of providing information and finding the shortest route from the point of travel. The result of this study is the application of an information system to determine the shortest route on a distance map using the dijkstra algorithm in Temanggung Regency.